A New Celtiberian Vascular Inscription from La Caridad (Caminreal, Teruel) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
The purpose of this article is to publish a new Celtiberian inscription recovered from the archaeological site of La Caridad de Caminreal (Teruel). It is inscribed on a locally produced vase that imitates a form of the Italic black-glazed ware (Lamboglia 2). The text, composed of four words, is the most extensive inscription on ceramic tableware documented to date at this site and in Celtiberia as a whole.
Keywords: Celtiberian language; epigraphy; La Caridad; instrumentum inscriptum; Celtiberia; graffiti; black gloss-finished pottery